Proceso atención de enfermería en adulto mayor con pie diabético. - Guamán Avilés, Ginger Katiusca (2023)
Diabetes mellitus is a metabolic pathology that, if not treated or controlled, can become chronic and complex, characterized by absolute or relative deficiency of insulin production in the body. This pathology is characterized by chronic hyperglycemia and other disorders of carbohydrate and lipid metabolism, on the other hand, diabetic foot is a complication that occurs in patients with a history of diabetes that causes damage to blood vessels. The present clinical case shows the care provided to an elderly female patient of 72 years of age, with a pathological history of diabetes mellitus grade II plus diabetic foot, whose main objective is to apply the nursing care process, and provide individualized care according to the patient's requirements, a comprehensive assessment of the patient was carried out using the functional patterns of the theorist Marjory Gordon, where 3 altered patterns were determined in the older adult, which are: Health Perception/Management, Nutritional and Metabolic, Adaptation/Stress Tolerance. Using the taxonomy of NANDA, NIC and NOC, priority nursing diagnoses will be developed consisting of Impairment of tissue integration, Risk of Infection, Risk of unstable glycemic level and optimal nursing interventions for the patient were established, which are presented below: Control of the patient's vital signs.- Inspect the skin for erythema, color or exudate.- Carry out correct asepsis of the area that is affected.- Blood glucose control.- Educate the patient about diabetic foot infections.- Maintain an intravenous line.- Administer medications prescribed by the doctor.- During his hospital stay, improvement was evident in the patient's state of health, control was maintained of both his blood glucose level and the state of the ulcer presented on the skin, daily asepsis of the affected area was performed and at the same time The patient was educated to promote self-care and maintain control of her pathology. Furthermore, a fundamental factor for the evolution of patients is the support from the family and in this case it was no exception, since the older adult had the support of the family from the first day of hospitalization, which I created a positive impact on his recovery. The nursing staff is the fundamental pillar in this care, based on the promotion and prevention of the disease. Her evolution was optimal until the day of her medical discharge and she was referred to the nearest health center to control her pathology.